DELYS: a novel microworld-based educational software for teaching computer science subjects - Dagdilelis, Vassilios; Evangelidis, Georgios; Satratzemi, Maya; Efopoulos, Vassilios; Zagouras, Charalabos (Computers and education, 2003)
The Greek ministry of education with the support of the European Union has begun an attempt to incorporate information and communication technology in the normal, everyday activities of secondary education. Part of this effort is the development of pilot educational software. Our project proposal was DELYS, an educational software environment that aids the teaching of computer science in secondary education. It was one of the approved proposals and, incidentally, the only one funded in the field of computer science. DELYS consists of four “exploratory microworlds” which deal with the following subjects: (1) the various components of a computer and how they operate as a whole, (2) the booting process in a computer, (3) the way data is represented numbers are processed, and (4) a programming environment. The material is mainly presented through the use of simulations and animations and it is accompanied by text and/or video. In this paper, we present the design rationale of the system and its description. In addition, we present initial evaluation results of DELYS with data collected from students and teachers. It must be stated that these first results of DELYS are most encouraging.